2020
DOI: 10.1002/jmri.27136
|View full text |Cite
|
Sign up to set email alerts
|

MRI Follow‐up of Astrocytoma: Automated Coregistration and Color‐Coding of FLAIR Sequences Improves Diagnostic Accuracy With Comparable Reading Time

Abstract: Background MRI follow‐up is widely used for longitudinal assessment of astrocytoma, yet reading can be tedious and error‐prone, in particular when changes are subtle. Purpose/Hypothesis To determine the effect of automated, color‐coded coregistration (AC) of fluid attenuated inversion recovery (FLAIR) sequences on diagnostic accuracy, certainty, and reading time compared to conventional follow‐up MRI assessment of astrocytoma patients. Study Type Retrospective. Population In all, 41 patients with neuropatholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In our study, we found a higher overall reading time including application loading times when using the ACC software, a finding that contrasts with previous studies reporting comparable or shorter reading times with this software. 15,16 While the shorter time required for the readout itself is in line with previous studies, the overall higher assessment time we found is most likely because we used 3D image acquisitions, which require higher processing power. The time required for loading and processing the images for ACC is certainly, in part, dependent on the computing power of the workstation and servers used.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In our study, we found a higher overall reading time including application loading times when using the ACC software, a finding that contrasts with previous studies reporting comparable or shorter reading times with this software. 15,16 While the shorter time required for the readout itself is in line with previous studies, the overall higher assessment time we found is most likely because we used 3D image acquisitions, which require higher processing power. The time required for loading and processing the images for ACC is certainly, in part, dependent on the computing power of the workstation and servers used.…”
Section: Discussionsupporting
confidence: 86%
“…Our results are in line with previous studies investigating different software using similar concepts of automated coregistration and highlighting of lesion changes as well as studies using the same software for longitudinal evaluation of lesion changes in FLAIR images. 13,15,16,18 Galletto Pregliasco et al 15 found a higher sensitivity and subjective confidence in the detection of new lesions on MR imaging of patients with multiple sclerosis using automated coregistration and a colored overlay map to depict lesion development. Lennartz et al 16 reported a higher sensitivity and diagnostic accuracy for the longitudinal assessment of astrocytomas in FLAIR sequences, in particular for subtle changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite an evident need for compensation strategies, recent high innovation on the MRI technology side and related demands remain mostly unanswered by diagnostic image assessment, which is still widely based on simple visual reading. In keeping with this imbalance, we are aware of only one previous study for neurooncological imaging that evaluated an approach based on SMs that was seamlessly integrated in the routine setting [32]. However, in this previous retrospective study, a smaller cohort consisting of 41 patients with different entities of glioma was considered, and these patients were scanned with various, inhomogeneous MRI protocols on various scanners from different manufacturers, with field strengths of scanners ranging between 1 and 3 Tesla [32].…”
Section: Discussionmentioning
confidence: 99%